Pengaruh Gaya Belajar terhadap Tingkat Prestasi Belajar Remaja di Bukittinggi - Kania Jeanrita; Tiara Eristina; Deby Amanda Putri; Ilham Fitra (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This research was studied in order to describe how the influence of learning types consisting of visual, audiotorial, and kinesthetic learning types on the learning achievement of young students in Bukittinggi. How to collect data in research through questionnaires and documentation. Shiva who is 15-18 years old is the population in this study. There were 100 participants in this study who were selected through the cluster random sampling technique. This hypothesis was tested through linear regression analysis with a gain of 0.07. The results of this study indicate that there is a significant influence between each learning style, namely visual, audiotorial, and kinesthetic learning styles on student learning outcomes in Bukittinggi. This is indicated by the results of the visual learning style determination test with a percentage of 21.37%, 54.70% auditory learning style, and 23.93% kinesthetic learning style.